Strategies for Improving the Quality of Private Higher Education Institutions Using the SWOT and PESTEL Approaches - Deden Prayitno, (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Abstract: The quality of private universities in Indonesia still shows significant disparities. Some institutions have successfully improved the quality of their academic services and gained recognition thru excellent accreditation, while many others have fallen behind due to weak strategic planning and sustainable quality management. This difference poses serious challenges in achieving equitable access to quality higher education. One of the essential instruments that every university must implement is the Internal Quality Assurance System (IQAS), What is commonly known in the university environment is the Internal Quality Assurance System (SPMI), designed to maintain consistency in quality standards thru the Planning, Implementation, Evaluation, Control, and Improvement (PIECI) cycle, or also known as PPEPP . However, the implementation of SPMI often faces obstacles, ranging from non-compliance with standards and weak evaluation to minimal involvement of work units and leaders in the quality culture. This article aims to analyze the factors causing quality inequality and formulate adaptive improvement strategies thru PESTEL and SWOT analysis. The research method uses a descriptive-qualitative approach with a case study at a private university experiencing obstacles in implementing SPMI (Internal Quality Assurance System). The analysis results show that the inability to anticipate external changes and weak internal governance have led to quality stagnation, low effectiveness of self-evaluation, and limited competitiveness. This article offers a PESTEL and SWOT-based strategic framework to help private colleges build a more integrated, adaptive, and sustainable quality system to strengthen accreditation and enhance competitiveness at both national and international levels. Keywords: SPMI, higher education, PESTEL and SWOT analysis.